2021
DOI: 10.1371/journal.ppat.1009546
|View full text |Cite
|
Sign up to set email alerts
|

The peptidoglycan-associated protein NapA plays an important role in the envelope integrity and in the pathogenesis of the lyme disease spirochete

Abstract: The bacterial pathogen responsible for causing Lyme disease, Borrelia burgdorferi, is an atypical Gram-negative spirochete that is transmitted to humans via the bite of an infected Ixodes tick. In diderms, peptidoglycan (PG) is sandwiched between the inner and outer membrane of the cell envelope. In many other Gram-negative bacteria, PG is bound by protein(s), which provide both structural integrity and continuity between envelope layers. Here, we present evidence of a peptidoglycan-associated protein (PAP) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…WGA, also known to bind GlcNAc, was recently shown to bind to sacculi of Borrelia burgdorferi . 42 Treatment of the fecal sacculi with fluorescent WGA resulted in a 120-fold increase in fluorescence, which suggests that the material has GlcNAc ( Figure 2D ), similar to that of Lactobacilli cultured in vitro ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 81%
“…WGA, also known to bind GlcNAc, was recently shown to bind to sacculi of Borrelia burgdorferi . 42 Treatment of the fecal sacculi with fluorescent WGA resulted in a 120-fold increase in fluorescence, which suggests that the material has GlcNAc ( Figure 2D ), similar to that of Lactobacilli cultured in vitro ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 81%
“…Although the effects of oxidative and nitrosative stress on peptidoglycan are poorly understood, a few studies reported links between oxidative or nitrosative stress and proteins associated with peptidoglycan or its synthesis [ 67 , 68 , 69 , 70 ]. The clearest demonstrated effect of oxidative stress on peptidoglycan comes from a recent study by Giacomucci et al This study showed that the absence of the protein ElyC of unknown function induces the overproduction of OH • in the periplasm, which leads to a direct or indirect interruption of peptidoglycan synthesis [ 71 ].…”
Section: Reactive Oxygen and Nitrogen Species: A Complex Reactions Ne...mentioning
confidence: 99%
“…Notably, expression of napA increased after 24h exposure to doxycycline (Table 1). This transcript encodes a periplasmic protein (also called BicA) that can bind copper and manganese, and associates with cell wall peptidoglycan [52][53][54]. The predicted sequence of NapA is similar to the Dps proteins of other bacterial species, which are involved with protecting DNA from stresses [55], although borrelia NapA lacks the Dps sequences that are involved with DNA-binding [52].…”
Section: Plos Onementioning
confidence: 99%
“…The predicted sequence of NapA is similar to the Dps proteins of other bacterial species, which are involved with protecting DNA from stresses [55], although borrelia NapA lacks the Dps sequences that are involved with DNA-binding [52]. NapA derives its name from neutrophil attracting protein A, and has been demonstrated to enhance immune responses [52,54,[56][57][58]. It remains to be seen whether differential expressionof NapA occurs during doxycycline treatment in the context of mammalian infection.…”
Section: Plos Onementioning
confidence: 99%